2007
DOI: 10.1586/14737175.7.10.1375
|View full text |Cite
|
Sign up to set email alerts
|

Current issues and trends in the diagnosis and treatment of adults with ADHD

Abstract: Attention-deficit/hyperactivity disorder (ADHD) has been commonly thought of as a childhood disorder that diminished over time. It is one of the most common developmental disorders and it is estimated that ADHD affects 5-10% of children. Two-thirds of children with ADHD will continue to have symptoms of ADHD that persist throughout adolescence. Longitudinal studies have demonstrated that symptoms of ADHD can also remain in adulthood, affecting 4.4% of the adult population. However, diagnosing adults with ADHD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 91 publications
0
12
0
1
Order By: Relevance
“…Other investigators have reported similar results. [5][6][7]24 The converse is also true. ADHD is found frequently in adult probands with depressive disorders.…”
Section: Key Learning Issue #1: Adhd Persists Into Adulthoodmentioning
confidence: 85%
See 4 more Smart Citations
“…Other investigators have reported similar results. [5][6][7]24 The converse is also true. ADHD is found frequently in adult probands with depressive disorders.…”
Section: Key Learning Issue #1: Adhd Persists Into Adulthoodmentioning
confidence: 85%
“…17 Another study of 104 boys with ADHD found that 11% had disabling ADHD in adulthood. 17,18 Other studies have reported that 60% of children with ADHD will exhibit sub-clinical symptoms of ADHD 4,6,[19][20][21][22] in adulthood. ADHD is best understood as a childhood-onset neurodevelopmental disorder that may persist into adulthood.…”
Section: Key Learning Issue #1: Adhd Persists Into Adulthoodmentioning
confidence: 99%
See 3 more Smart Citations